Role of interleukin-17 in the pathogenesis of rheumatoid arthritis - Jeffrey A Ongkowijaya; Bambang Setiyohadi; Sumariyono Sumariyono; Yoga I Kasjmir (Indonesian Journal of Rheumatology, 2010)
Rheumatoid arthritis (RA) is a systemic autoimmune disorder with an unknown etiology. It typically affects the peripheral synovial joints symmetrically. The roles of T and B cells, macrophages, plasmocytes, host tissue cells (synoviocytes, chondrocytes), and osteoclastsin RA are more defi ned. In RA, cytokines secreted by cells implicated in adaptive and natural immunity have important roles in causing infl ammation, articular destruction, and other comorbid diseases related to RA. Other than the clear roles of interleukin (IL)-1 and tumor necrosis factor Î±, there are other cytokines that are suspected of having roles in the pathogenesis of RA, IL-17 for instance. Interleukin-17 is a proinfl ammatory cytokine,Â  produced by Th17 cells, and has pleiotropic effects on various cells contributing to the pathogenic condition of RA. Several studies showed that this cytokine maintains the infl ammation and causes more destruction of joint cartilage. Advances in the understanding of the role of IL-17 elicits the idea to modulate IL-17 and/or Th17 cells as the potential targetsof therapy in RA